Изделия из текстиля на городище Самосделка - Зиливинская, Э.Д.; Орфинская, О.В. (Степи Европы в эпоху средневековья, 2009)
The paper is devoted to examination of textiles fragments found at Samosdelka hillfort in Astrakhan province. The town located on an island in the Volga estuary was founded in the Khazar time not later than in the 9'1' century and existed continuously until 1330s. Some data collected by now permit to relate it to the capital of Khazar Qaganate - Itil, which has not been found so far.